Catalytic olefin epoxidation with cationic molybdenum(VI) cis-dioxo complexes and ionic liquids - Gago, Sandra; Balula, Salete S.; Figueiredo, Sonia; Lopes, Andre D.; Valente, Anabela A.; Pillinger, Martyn; Goncalves, Isabel S. (Applied Catalysis a-General, 2010)
n/a
Times Cited: 19 Balula, Salete/B-7508-2012; Lopes, Andre/E-2136-2012; Figueiredo, Sonia/E-4355-2012; Gago, Sandra/H-5413-2012; Pillinger, Martyn/H-2639-2013; Goncalves, Isabel/H-3742-2013; Valente, Anabela/H-5922-2013; REQUIMTE, PHOTO/M-4229-2013; REQUIMTE, MAT/M-4540-2013; REQUIMTE, NSF/N-1636-2013; CIQA, CIQA/N-6549-2013; REQUIMTE, LAQV/N-9835-2013 Balula, Salete/0000-0002-8984-0473; Lopes, Andre/0000-0002-9702-1216; Gago, Sandra/0000-0003-0221-8508; Pillinger, Martyn/0000-0002-6243-7692; Goncalves, Isabel/0000-0002-2836-7715; 19